Advances of Carbon-Based Materials for Lithium Metal Anodes - Tang, Kaikai; Xiao, Jun; Li, Xiao; Wang, Dandan; Long, Mengqi; Chen, Jun; Gao, Hong; Chen, Weihua; Liu, Chuntai; Liu, Hao (Frontiers in Chemistry, 2020)
Lithium metal with high theoretical specific capacity (3860 mAh g-1), low mass density, and low electrochemical potential (-3.040 V vs SHE) is an ideal candidate of the battery anode. However, the challenges include dendrite propagation, volume fluctuation, and unstable solid electrolyte interphase of lithium metal during the lithium plating impede the practical development of Lithium metal batteries (LMBs). Carbon-based materials with diverse structures and functions are ideal candidates to address the challenges in LMBs. Herein, we briefly summarize the main challenges as well as the recent achievements of lithium metal anode in terms of utilizing carbon-based materials as electrolyte additives, current collectors and composite anodes. Meanwhile, we propose the critical challenges that need to be addressed and perspectives for ways forward to boost the advancement of LMBs.